Power system analysis educational toolbox using Matlab 7.1 - Mohd Azzuan, Abd Aziz (2008)
This Power System Analysis toolbox by using MATLAB GUI has been developed by the author to assist in typical Power System Analysis. The one of the objectives of this project is to develop an educational toolbox for Electrical Power System students and lecturers in order to solve some of Power System problems such as Power Flow Analysis, Fault Analysis, Optimal Dispatch of Power Generation, and lastly is, Steady State and Transient Stability Analysis. All this kinds of problems consists of various methods of mathematical calculation which is difficult to perform by using manual calculation (formula and calculator). The existence of this educational toolbox will help the user to calculate the calculation become more faster and easier. This educational toolbox was developed by using MATLAB 7.1 software (M-File and Graphical User Interface). MATLAB, with its extensive numerical resources, can be used to obtain numerical solutions that involve various types of vector-matrix operations. This Power System educational toolbox allows the user especially students to analyze and design power systems without having a lot of calculation.